PENGATURAN PERLINDUNGAN HUKUM KORBAN DELIK ADAT LOKIKA SANGGRAHA - DEWI, NI MADE LIANA (Kerta Dyatmika, 2016)
ABSTRACTÂ Lokika customs act offenses Sanggraha in Bali, there is no regulation in the various laws and regulations that exist in Indonesia, especially in the Criminal Code so that women as victims do not receive legal protection. Acts cohabiting is an act that is equated with the offense customary lokika Sanggraha so it can be seen in the Emergency Law No. 1 of 1951 Article 5, paragraph (3) sub b, that there are two categories in the formulation of the word "laws of life", namely: first , criminal customary law that has padanaan the criminal Code so threatened with sanctions contained in the Criminal Code. And second, do not have padanaan or comparison of the Criminal Code, so it may be subject to Article 5, paragraph (3) sub b of Emergency Law No. 1 of 1951 with penalties of not more than three months in prison or a fine of 500 rupees.Â Keywords: Legal Protection, Indigenous offense, Lokika Sanggraha